Global inverse optimal control of vertical take-off and landing aircraft. (March 2021) - Do, K.D.
Abstract: This paper formulates and solves a new problem of global practical inverse optimal control of underactuated vertical take-off and landing (VTOL) aircraft. The control design is based on a recent development of inverse optimal control design for nonlinear systems, and ensures global practical K ∞ -exponential stability of stabilization errors. More importantly, it also minimizes a cost function that penalizes both stabilization errors and control inputs without having to solve a Hamilton–Jacobi–Bellman or Hamilton–Jacobi–Isaacs equation.